Recruiting participants to a randomized controlled trial testing an intervention in palliative cancer care – The perspectives of health care professionals. (December 2017) - Holm, Maja; Alvariza, Anette; Fürst, Carl-Johan; Wengström, Yvonne; Årestedt, Kristofer; Öhlen, Joakim; Goliath, Ida
Abstract: Purpose: The recruitment of participants to randomized controlled trials (RCTs) in palliative cancer care by health care professionals is often unsuccessful, which could result in failure to achieve study power. The purpose of this paper is to describe how health care professionals experienced recruiting patients and family caregivers to an RCT in palliative cancer care. Methods: The study had a qualitative explorative design. Ten palliative home care settings were involved in the RCT and data were generated through focus group discussions and interviews with health care professionals who were responsible for the recruitment. The transcripts were analyzed with interpretive descriptive principles. Results: The experiences of the health care professionals reveal that communicating the RCT-design to patients and family caregivers was a challenging part of the recruitment but was considered a process of learning over time. The delicate situation that participants were living under added to the challenge and health care professionals believed that the randomized design was contrary to their normal approach to always offer the best possible support. Conclusions: The results contribute valuable knowledge for future trials in palliative cancer care. To promote successful recruitment, health care professionals may be in need of more training to improve their communication skills and it may be necessary to consider other research designs than the RCT.